Cf/C composites: correlation between CVI process parameters and Pyrolytic Carbon microstructure - F. Burgio; P. Fabbri; G. Magnani; M. Scafè; L. Pilloni; A. Brentari; A. Brillante; T. Salzillo (Fracture and Structural Integrity)
Chemical Vapour Infiltration (CVI) technique has been long used to produce carbon/carbon composites. The Pyrolytic Carbon (Py-C) matrix infiltrated by CVI could have different microstructures, i.e. Rough Laminar (RL), Smooth Laminar (SL) or Isotropic (ISO). These matrix microstructures, characterized by different properties, influence the mechanical behaviour of the obtained composites. Tailoring the process parameters, it is possible to direct the infiltration towards a specific Py-C type. However, the factors, influencing the production of a specific matrix microstructure, are numerous and interconnected, e.g. temperature, pressure, flow rates etc. Due to the complexity of the physical and chemical phenomena involved in CVI process, up to now it has not been possible to obtain a general correlation between CVI process parameters and Py–C microstructure. This study is aimed at investigating the relationship between infiltration temperature and the microstructure of obtained Py-C, for a pilot - sized CVI/CVD reactor. Fixing the other process parameters and varying only the temperature, from 1100°C to 1300°C, the Py-C infiltration was performed on fibrous preforms. Polarized light microscopy, with quantitative measurements of average extinction angle (Ae), and Raman spectroscopy were used to characterize the obtained Py-C microstructures.